A cofacial metal–organic framework based photocathode for carbon dioxide reduction. Issue 10 (25th January 2021) - Ding, Bowen; Chan, Bun; Proschogo, Nicholas; Solomon, Marcello B.; Kepert, Cameron J.; D'Alessandro, Deanna M.
Abstract : The photocathode functionality of a Metal–Organic Framework (MOF) featuring cofacial photo- and electro-active ligands provides a new approach to CO2 reduction via charge transfer with a rhenium electrocatalyst. Abstract : Innovative and robust photosensitisation materials play a cardinal role in advancing the combined effort towards efficient solar energy harvesting. Here, we demonstrate the photocathode functionality of a Metal–Organic Framework (MOF) featuring cofacial pairs of photo- and electro-active 1, 4, 5, 8-naphthalenediimide (NDI) ligands, which was successfully applied to markedly reduce the overpotential required for CO2 reduction to CO by a well-known rhenium molecular electrocatalyst. Reduction of [Cd(DPNDI)(TDC)] n (DPNDI = N, N ′-di(4-pyridyl)-1, 4, 5, 8-naphthalenediimide, H2 TDC = thiophene-2, 5-dicarboxylic acid) to its mixed-valence state induces through-space Intervalence Charge Transfer (IVCT) within cofacial DPNDI units. Irradiation of the mixed-valence MOF in the visible region generates a DPNDI photoexcited radical monoanion state, which is stabilised as a persistent species by the inherent IVCT interactions and has been rationalised using Density Functional Theory (DFT). This photoexcited radical monoanion state was able to undergo charge transfer (CT) reduction of the rhenium molecular electrocatalyst to effect CO generation at a lower overpotential than that required by the discrete electrocatalyst itself. The exploitation of cofacial MOFs opens new directions for the design philosophy behind light harvesting materials.